The Tradition of Reading Fragments of QS. Al-Baqarah/2:127 in the Breakthrough Procession: Living Qur'an Study in Kaliwungu District, Kendal Regency - Muhamad A'thoillah Mubarok (International Journal of Sociology of Religion, 2026)
The Qur'an is not only understood as a text that is read and studied, but is also present in various socio-religious practices of the Muslim community. One form of reception is the tradition of reading QS quotes. al-Baqarah/2:127 at the groundbreaking procession in Kaliwungu District, Kendal Regency. This study aims to describe the implementation of the tradition of reading the verse and analyze the meaning and response of the community to the practice that develops in the midst of their socio-religious life. This research uses a qualitative approach within the framework of the study of Living Qur'an. Data was collected through observation, interviews, and documentation, then analyzed using descriptive-analytical techniques. The results of the study show that the tradition of reading QS. al-Baqarah/2:127 was held as part of a series of groundbreaking processions that began with an explanation of the history of the activity, followed by the recitation of verses related to the construction of the Kaaba by Prophet Ibrahim and Prophet Ismail, and ended with a joint prayer. For the community, the reading of the verse not only functions as a religious legitimacy for development activities, but is also interpreted as a form of self-approach to Allah, an expression of gratitude, a symbol of hope for blessings, and a medium for strengthening spiritual and collective values in society. These findings show that the Qur'an functions dynamically in the social life of the community through the ongoing process of reception and actualization of meaning.